ANALISIS USAHA TERNAK ITIK BERTELUR DI DESA TANJUNG MEDAN LABUHAN BATU SELATAN - Sanzae Nova; Dini Hariyati Adam; Yusmaidar Sepriani; Hilwa Walida (Agros Journal of Agriculture Science, 2023)
Duck farming needs to pay attention to the problems encountered in the process of raising ducks and efforts to deal with them need to be done. The purpose of this research is to analyze the business of laying ducks in Tanjung Medan, South Labuhanbatu Regency. This research was compiled based on a purposive survey method and primary data acquisition using questionnaires for duck breeders. This research found that in one period the farmer needs to spend IDR 20,000,000 capital with a livestock population of 150 heads. Income for 4 months ranges from IDR 21,450,000 Keywords: analysis, ducks, business, raising, laying eggsINTISARIBudidaya itik perlu diperhatikan masalah yang dihadapi dalam proses beternak dan perlu dilakukan upaya penanganan. Tujuan riset ini adalah melakukan analisis usaha ternak itik petelur di desa tanjung medan labuhanbatu selatan. Riset ini disusun berdasarkan metode survey secara purposive dan perolehan data primer dengan kuisioner kepada peternak itik. Riset ini memperoleh hasil bahwa dalam satu periode peternak perlu mengeluarkan modal Rp 20.000.000 dengan populasi ternak sebanyak 150 ekor. Penghasilan selama 4 bulan berkisar RP 21.450.000 Kata Kunci: analisis, itik, usaha, berternak, bertelur